Cost‐effectiveness of second‐line empagliflozin versus liraglutide for type 2 diabetes in the United States. Issue 4 (11th January 2022) - Reifsnider, Odette S.; Pimple, Pratik; Brand, Sarah; Bergrath Washington, Evelien; Shetty, Sharash; Desai, Nihar R.
Abstract: Aim: To estimate the cost‐effectiveness of sequential use of the sodium‐glucose co‐transporter‐2 inhibitor empagliflozin and glucagon‐like peptide‐1 receptor agonist liraglutide after metformin in patients with type 2 diabetes (T2D) from the US payer perspective. Materials and Methods: An economic simulation model with a lifetime horizon was developed to estimate T2D‐related complications (including cardiovascular [CV] death, myocardial infarction, stroke, and renal outcomes) using EMPA‐REG OUTCOME data or UK Prospective Diabetes Study risk equations, in patients with or without a history of cardiovascular disease (CVD), respectively. Evidence synthesis methods were used to provide effectiveness inputs for empagliflozin and liraglutide. Population characteristics, adverse event rates, treatment escalation, costs (2019), and utilities (both discounted 3%/year) were taken from US sources. Results: Compared with second‐line liraglutide in the overall T2D population, second‐line empagliflozin was dominant as it was associated with lower total lifetime cost (11 244/patient less) and resulted in a quality‐adjusted life‐year (QALY) gain (0.32/patient). Second‐line empagliflozin was associated with reductions in CV death (by 5%) and lower cumulative complication rates in patients with CVD (by 2%), relative to second‐line liraglutide. These findings were consistent among patients with co‐morbid CVD, with gains in incremental QALYs (0.43/patient) and lower lifetime cost (by 10 175/patient) relative to second‐line liraglutide. Scenario analyses consistently showed dominance for second‐line empagliflozin. Conclusion: For patients with T2D, use of second‐line empagliflozin combined with metformin was a dominant strategy for US payers, associated with extended survival, improved QALYs, and lower costs compared with second‐line liraglutide.